Complete Heart Block Induced by Hyperemesis: Integrating the Vagal Score to Guide Management and Avoid Invasive Interventions - Hermiz, Joshua; Mittal, Vivek; Raj, Kevin; Bhagat, Umesh; Gahona, Christian C. Toquica (British Journal of Healthcare and Medical Research, 2025)
Complete heart block (CHB) represents the complete absence of atrioventricular (AV) conduction between the atria and ventricles, preventing the sinoatrial node from regulating heart rate and cardiac output through communication with the AV node. Although standard treatment involves permanent pacemaker implantation, it is crucial to identify reversible causes such as electrolyte imbalances or vagal-mediated mechanisms, as it may allow for alternative, non-invasive management. This case report discusses a rare instance of hyperemesis-induced CHB and utilizes the "vagal score" via ECG-based assessments to determine approach to management, ultimately identifying reversible etiologies and preventing unnecessary invasive interventions such as permanent pacemaker placement.